Predictive value of endoscopic esophageal findings for residual esophageal cancer after neoadjuvant chemoradiotherapy - van der Bogt, Ruben D.; van der Wilk, Berend J.; Nikkessen, Suzan; Krishnadath, Kausilia K.; Schoon, Erik J.; Oostenbrug, Liekele E.; Siersema, Peter D.; Vleggaar, Frank P.; Doukas, Michael; van Lanschot, J. Jan B.; Spaander, Manon C. W. (Endoscopy, 2021)
Background Endoscopic evaluation of the esophageal mucosa may play a role in an active surveillance strategy after neoadjuvant chemoradiotherapy (nCRT) for esophageal cancer. This study investigated the yield of endoscopic findings for detection of residual disease.Methods Patients from the multicenter preSANO cohort, who underwent nCRT followed by surgery for esophageal or junctional cancer, were included. Upper endoscopy was performed 6 and 12 weeks after nCRT. Patients with residual disease at 6 weeks underwent immediate surgery. Endoscopic records were reviewed for presence of stenosis, suspicion of residual tumor, scar tissue, and ulceration. Presence and type of endoscopic findings were compared with outcome of the resection specimen.Results 118 of 156 patients (76 %) had residual disease in the resection specimen. Endoscopic suspicion of residual tumor was significantly associated with presence of residual disease. At 6 weeks, 40/112 patients with residual disease and 4/33 patients with complete response had endoscopic suspicion of residual tumor (36 % vs. 12 %; P = 0.01), while this was reported in 16/73 and 0/28 patients, respectively, at 12 weeks (22 % vs. 0 %; P < 0.01). Positive predictive value of endoscopic suspicion of residual tumor was 91 % at 6 weeks and 100 % at 12 weeks. Endoscopic findings of non-passable stenosis, passable stenosis, scar tissue, or ulceration were not associated with residual disease. Conclusions Endoscopic suspicion of residual tumor was the only endoscopic finding associated with residual disease. Based on its positive predictive value, this endoscopic finding may contribute to the diagnostic strategy used in active surveillance.